The extensive margin of exporting products: A firm-level analysis - Costas Arkolakis; Marc-Andreas Muendler (Center for Economic Studies and ifo Institute (CESifo), 2010)
We use a panel of Brazilian exporters, their products, and destination markets to document a set of regularities for multi-product exporters: (i) few top-selling products account for the bulk of a firm's exports in a market, (ii) the distribution of exporter scope (the number of products per firm in a market) is similar across markets, and (iii) within each market, exporter scope is positively associated with average sales per product. Our data also show that firms systematically export their highest-sales products across multiple destinations. To account for these regularities, we develop a model of firm-product heterogeneity with entry costs that depend on exporter scope. Estimating this model for the within-firm sales distribution we identify the nature and components of product entry costs. We find that firms face a strong decline in product sales with scope but also that market-specific entry costs drop fast. Counterfactual experiments with globally falling entry costs indicate that a large share of the simulated increase in trade is attributable to declines in the firm's entry cost for the first product.
Keywords: F12; L11; F14; 330; international trade; heterogeneous firms; multi-product firms; firm and product panel data; Brazil; Internationale Handelspolitik; Unternehmenspolitik; Export; Produktdifferenzierung; Brasilien